2020
DOI: 10.46554/1993-0453-2020-5-187-97-105
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Non-Financial Reporting: International and Russian Practice

Abstract: Ñàìàðñêèé ãîñóäàðñòâåííûé ýêîíîìè÷åñêèé óíèâåðñèòåò.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…As our study has shown, companies in the construction sector actively use debt financing, regardless of financial constraints, which does not confirm the results of [6]. For large companies, the share of loan financing is about 60%, for medium-sized companies up to 90%, and for small companies 70%.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…As our study has shown, companies in the construction sector actively use debt financing, regardless of financial constraints, which does not confirm the results of [6]. For large companies, the share of loan financing is about 60%, for medium-sized companies up to 90%, and for small companies 70%.…”
Section: Discussioncontrasting
confidence: 85%
“…For the funding party, information transparency is a risk factor that affects the efficiency of funding. That is why, despite the studies devoted to evaluating of Russian companies financing structure [5], financial constraints that affect investment decisions of Russian companies [6] and construction companies, in particular, the issues of interrelation between the level of financial transparency and the financial position of companies [7] remain essential.…”
Section: Introductionmentioning
confidence: 99%